Outcome Analysis of End-to-End and End-to-Side Anastomoses in 131 Patients Undergoing Microsurgical Free Flap Reconstruction of the Lower Extremity - Könneker, Sören; Broelsch, G.F.; Kuhbier, J.W.; Framke, T.; Neubert, N.; Dastagir, K.; Mett, T.; Vogt, P.M.; Jokuszies, A. (Journal of Reconstructive Microsurgery Open, 2017)
Background End-to-end and end-to-side anastomoses remain the most common techniques in microsurgical free flap reconstruction. Still, there is an ongoing effort to optimize established techniques and develop novel techniques. Numerous comparative studies have investigated flow dynamics and patency rates of microvascular anastomoses and their impact on flap survival. In contrast, few studies have investigated whether the type of anastomosis influences the outcome of microvascular free flap reconstruction of a lower extremity.Patients and Methods Retrospectively, we investigated the outcome of 131 consecutive free flaps for lower extremity reconstruction related to the anastomotic technique.Results No statistical significance between arterial or venous anastomoses were found regarding the anastomotic techniques (p = 0.5470). However, evaluated separately by vessel type, a trend toward statistical significance for anastomotic technique was observed in the arterial (p = 0.0690) and venous (p = 0.1700) vessels. No thromboses were found in arterial end-to-end anastomoses and venous end-to-side anastomoses. More venous (n = 18) than arterial thromboses (n = 9) occurred in primary anastomoses undergoing microsurgical free flap reconstruction (p = 0.0098). Flap survival rate was 97.37% in the end-to-end arterial group versus 86.36% in the end-to-side group. No thromboses were found in five arterial anastomoses using T-patch technique.Conclusion For lower extremities, there is a connate higher risk for venous thrombosis in anastomotic regions compared with arterial thrombosis. We observed divergent rates for thromboses between end-to-end and end-to-side anastomoses.However, if thrombotic events are explained by anastomotic technique and vessel type, the latter carries more importance.
Keywords: free flap reconstruction; end-to-end anastomosis; end-to-side anastomosis